2021
DOI: 10.1002/jbm4.10526
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Sglt2 Deletion on Bone and Mineral Metabolism in Mice

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In an animal model, a long-term (25 weeks) inhibition of sodium-glucose cotransporter-2 did not modulate VD concentrations but it contributed to increased bone fragility [44]. In human studies, dapagliflozin did not affect VD concentrations [45], while canagliflozin decreased them (via a rapid increase in the serum phosphorus, fibroblast growth factor 23 and parathormone levels, with a potentially negative impact on bone health) [41] and empagliflozin slightly increased VD concentrations [46].…”
Section: Discussionmentioning
confidence: 90%
“…In an animal model, a long-term (25 weeks) inhibition of sodium-glucose cotransporter-2 did not modulate VD concentrations but it contributed to increased bone fragility [44]. In human studies, dapagliflozin did not affect VD concentrations [45], while canagliflozin decreased them (via a rapid increase in the serum phosphorus, fibroblast growth factor 23 and parathormone levels, with a potentially negative impact on bone health) [41] and empagliflozin slightly increased VD concentrations [46].…”
Section: Discussionmentioning
confidence: 90%
“…Clinical studies have found that SGLT2 inhibitors improve heart failure and cardiovascular outcomes in patients with T2DM ( 36 ). Evidence also showed that SGLT2 inhibitors may slightly increase calcium levels by reducing urinary calcium excretion ( 37 , 38 ). This evidence suggests that SGLT2 inhibitors may be beneficiary for T2DM patients with CAN, but further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of SGLT2 has been reported to potentially improve glucose control but may increase the risk of infection, malnutrition, and mortality [ 17 ]. The mutant mice showed normal serum calcium and phosphate, parathyroid hormone, vitamins D, and fibroblast growth factor levels [ 55 ]. Although no changes in trabecular or cortical bone micro-structure were observed in Sweet Pee mice, a decrease in cortical bone mineral density was reported compared to wild-type mice at 25 weeks [ 55 ].…”
Section: Renal Glucosuria Models In Experimental Animalsmentioning
confidence: 99%
“…The mutant mice showed normal serum calcium and phosphate, parathyroid hormone, vitamins D, and fibroblast growth factor levels [ 55 ]. Although no changes in trabecular or cortical bone micro-structure were observed in Sweet Pee mice, a decrease in cortical bone mineral density was reported compared to wild-type mice at 25 weeks [ 55 ]. Loss of SGLT2 function in mice may contribute to long-term bone fragility.…”
Section: Renal Glucosuria Models In Experimental Animalsmentioning
confidence: 99%